Correlation of Nonthyroidal Illness Syndrome with Extubation Outcome in Mechanically Ventilated Children: A Prospective Cohort Study - Abdelaziz, Tarek A.; Romih, Mohamed Mahmoud; Ismail, Weaam Ibrahim; Emhalhal, Khadija A.L. Mabrouk; Baz, Eman Gamal (Journal of Pediatric Intensive Care, 2022)
This study aimed to assess the relationship between non-thyroidal illness syndrome (NTIS) and extubation outcomes in pediatric patients requiring mechanical ventilation. This prospective cohort study included 59 patients who underwent mechanical ventilation in the pediatric intensive care unit of a tertiary care university hospital from July 2020 to June 2021. Each patient underwent laboratory testing including serum levels of thyroid-stimulating hormone (TSH), free T3 (fT3), free T4 (fT4), and reverse T3 (rT3) on the first and third days of mechanical ventilation. On the first day of mechanical ventilation, 62.7% of patients had low fT3, which significantly increased to 78% of patients on the third day. In comparison to values on day one, median levels of fT3 and fT4 significantly decreased and rT3 significantly increased on day three. However, no significant differences were found in the median TSH levels over the same time span. Thirty-five patients (59%) survived while 24 patients (41%) did not survive. Compared with survivors, non-survivors had significantly higher median serum TSH levels on day one, while all other thyroid function tests assays did not significantly differ between days one and three. Of note, serum TSH, fT3, fT4, and rT3 levels, on the first and third days, did not differ significantly between patients who experienced extubation failure and extubation success. To the best of our knowledge, this is the first study to examine thyroid function values in mechanically ventilated children to determine their correlation with extubation outcomes. In this study, NTIS did not correlate with extubation outcomes in critically ill children undergoing mechanical ventilation.
Keywords: extubation outcome; mechanical ventilation; nonthyroidal illness syndrome; reverse T3; thyroid hormones